Aesthetics as Phenomenology : The Appearance of Things - Figal, Günter, 1949- (Book collections on Project MUSE., 2015)
Connecting aesthetic experience with our experience of nature or with other cultural artifacts, Aesthetics as Phenomenology focuses on what art means for cognition, recognition, and affect-how art changes our everyday disposition or behavior. Günter Figal engages in a penetrating analysis of the moment at which, in our contemplation of a work of art, reaction and thought confront each other. For those trained in the visual arts and for more casual viewers, Figal unmasks art as a decentering experience that opens further possibilities for understanding our lives and our world.